Modern banking system of Ukraine and main problems of its development - Глущенко, Віктор Володимирович; Соловйов, Денис Михайлович (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
Current state of banking system being the important factor for stability and development of economic life of the country is elucidated in the article. The fundamental causes of the banking crisis as well as the main problems of banking sector and economic development of the whole country are revealed in it. It can be noted that systemic banking crisis is the result of interlacing of three groups of problems: the longstanding structural and institutional disproportions in the economy of Ukraine; systemic problems of banking system; abrupt aggravation of problems in banking system in 2014 under the influence of force-majeure factors in foreign policy and shocks caused by wrong actions of monetary regulator. Macroeconomic priorities for development of Ukrainian economy, intensive development of high-technology industry, science, technical and technological innovations being the main one of these priorities, as well as their implementation into industry and delivery for internal and external markets are presented in the article. The system of strategic and tactic actions for getting out of the crisis, as well as for developing of the banking sector and achieving macroeconomic priorities is also proposed in the article. The crucial tasks of economic policy should be as follows: cardinal improvement of the quality of public administration at the level of top-management officials in the government, National Bank and otherinstitutions of authority; development of packaged strategies and programs for the formation of effective industrial policy of Ukraine; prolongation of moratorium on agricultural lands privatization until the end of the crisis and prosperity growth of the population for enabling full-fledged participation of society in the future privatization. The first-priority steps to reduce systemic risks should be as follows: urgent appointment of high-professional and independent staff to the Board of Ukrainian National Bank and the improvement of juridical mechanisms of its influence on the  Ukrainian National Bank management; performance of the reform of the National Bank concerning monetary and currency regulation that should be based on transition from dominance of constant-access operations to discretionary monetary policy. Under such conditions it will be possible to provide transition to flexible inflation targeting regime being the optimal compromise ensuring price stability and stimulating economic growth.